1987
DOI: 10.1210/endo-120-6-2488
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxycholecalciferol Receptor Regulation in Hormonally Induced Differentiation of Mouse Mammary Gland in Culture*

Abstract: Mammary explants from pregnant mouse cultured in the presence of insulin, cortisol, and PRL express their differentiated function by producing milk proteins such as casein. Sucrose density gradient analysis of high salt extract of cultured explants showed the presence of 1,25-dihydroxycholecalciferol (1,25-(OH)2D3 specific binding activity sedimenting at 3.3 S. Specific 1,25-(OH)2D3 binding activity in mammary explants varied as a function of the hormonal milieu in culture. The highest activity was found in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Studies in experimental animals have demonstrated that the VDR is dynamically regulated during pregnancy and lactation, but little is known about its specific functions. The VDR is expressed at low levels in mammary gland in virgin rats and is upregulated in response to the differentiation inducing hormones cortisol, prolactin and insulin (Mezzetti et al 1987). Highest levels of VDR in mammary gland are seen during lactation, being maximal at 3 days post partum when the concentration of calcium in milk is highest (Colston et al 1988).…”
Section: Vdr Expression In Mammary Tissue and Breast Tumoursmentioning
confidence: 99%
“…Studies in experimental animals have demonstrated that the VDR is dynamically regulated during pregnancy and lactation, but little is known about its specific functions. The VDR is expressed at low levels in mammary gland in virgin rats and is upregulated in response to the differentiation inducing hormones cortisol, prolactin and insulin (Mezzetti et al 1987). Highest levels of VDR in mammary gland are seen during lactation, being maximal at 3 days post partum when the concentration of calcium in milk is highest (Colston et al 1988).…”
Section: Vdr Expression In Mammary Tissue and Breast Tumoursmentioning
confidence: 99%
“…The dynamic regulation of VDR in mammary gland during the reproductive cycle suggests that hormones and/or growth factors which impact on glandular development may modulate VDR expression under physiologic conditions. Indeed, lactogenic hormones upregulate VDR in normal mammary gland and nontransformed mammary cells in vitro [87,125]; however, the specific factors responsible for VDR regulation in the normal mammary gland have yet to be defined.…”
Section: Vitamin D and Prevention Of Breast Cancer Expression And Rolmentioning
confidence: 99%
“…The addition of vitamin D3 significantly increases casein production in mouse mammary explants cultured in the presence of insulin, cortisol, and prolactin (175). Moreover, Bhattacharjee et al found that mammary gland explants from rachitic rats and mice show a decreased production of milk proteins when cultured in the presence of insulin, prolactin, and glucocorticoid (176).…”
Section: Vitamin D3mentioning
confidence: 99%
“…The action of vitamin D3 is specifically directed to the epithelial cells, that have been shown to concentrate the hormone in their nuclei (177). In addition, mouse mammary epithelial cells have been shown to possess specific vitamin D receptors, the level of which is enhanced by insulin, prolactin, and glucocorticoid (178). These data strongly suggest that vitamin D3 at physiological concentrations may be involved in the control of lactogenesis.…”
Section: Vitamin D3mentioning
confidence: 99%